2021
DOI: 10.3389/fpsyt.2020.616501
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Lateral Habenula Deep Brain Stimulation for Treatment-Resistant Depression

Abstract: Treatment-resistant depression (TRD) is a chronic and severe psychiatric illness associated with limited therapeutic options. Deep brain stimulation (DBS) is a promising therapy for TRD patients. However, its safety and efficacy are still unclear. Here we reported the safety and efficacy of lateral habenula (LHb) DBS for a TRD patient who had failed medical, psychological, electroconvulsive, and ketamine therapy. The DBS system is compatible with 3T magnetic resonance imaging along with local field potential (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Specific patterns of acute and chronic electrical stimulation ( Li et al, 2011 ; Meng et al, 2011 ; Tchenio et al, 2017 ) or pharmacological inhibition ( Winter et al, 2011 ) of the habenula attenuate MDD-like behaviors in animal models. This is further supported by a recent case report study showing improvement of symptoms with deep brain stimulation of the habenula in treatment-resistant MDD patients ( Wang et al, 2020 ). In contrast, human neuroimaging and postmortem studies have been inconsistent.…”
Section: Habenula In Adhd and Mddsupporting
confidence: 69%
“…Specific patterns of acute and chronic electrical stimulation ( Li et al, 2011 ; Meng et al, 2011 ; Tchenio et al, 2017 ) or pharmacological inhibition ( Winter et al, 2011 ) of the habenula attenuate MDD-like behaviors in animal models. This is further supported by a recent case report study showing improvement of symptoms with deep brain stimulation of the habenula in treatment-resistant MDD patients ( Wang et al, 2020 ). In contrast, human neuroimaging and postmortem studies have been inconsistent.…”
Section: Habenula In Adhd and Mddsupporting
confidence: 69%
“…The full text search of the remaining 75 studies 25 did not target the Hb, 44 described preclinical experiments and one study described data reported in an earlier manuscript. After screening, this systematic review identified five articles (Table 2) (47,(63)(64)(65)(66) that satisfied the inclusion criteria. These articles reported the results of DBS targeting the Hb for four different indications: schizophrenia (63), treatment resistant major depressive disorder (TRD) (47,65,66), OCD (45) and BD (46).…”
Section: Resultsmentioning
confidence: 99%
“…After screening, this systematic review identified five articles (Table 2) (47,(63)(64)(65)(66) that satisfied the inclusion criteria. These articles reported the results of DBS targeting the Hb for four different indications: schizophrenia (63), treatment resistant major depressive disorder (TRD) (47,65,66), OCD (45) and BD (46).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations